FLIPPED CLASSROOM MODEL IN HINDU RELIGIOUS AND CHARACTER EDUCATION LEARNING AT SMA NEGERI 1 KENDARI - I Ketut Winantra; Maya Ayuning Ati (UHN I Gusti Bagus Sugriwa Denpasar, 2026)
Improving the effectiveness of Hindu Religious and Character Education requires an instructional model that actively engages students in the learning process. One innovative approach applied is the flipped classroom model, which shifts learning from a teacher-centered paradigm to a student-centered one by encouraging independent study prior to classroom interaction. This study aims to analyze: (1) the rationale for implementing the flipped classroom model in Hindu Religious and Character Education at SMA Negeri 1 Kendari, (2) the process of its implementation, and (3) the implications of its application for student learning outcomes. This research is grounded in meaningful learning theory, constructivist theory, and humanistic learning theory. A qualitative descriptive method was employed, with data collected through observations, in-depth interviews, and document analysis. The findings reveal that the flipped classroom model significantly enhances student engagement and conceptual understanding. Students who access learning materials independently through videos and modules demonstrate better preparedness for classroom discussions and problem-solving activities. The teacher’s role evolves into that of a facilitator, mentor, and motivator who provides guidance and feedback. Moreover, the implementation of the flipped classroom model positively influences students’ cognitive, affective, and psychomotor domains, contributing to the development of independent, creative, religious, and responsible character traits.